PENGEMBANGAN POTENSI PERAIRAN KUALA BUBON PADA NELAYAN KEPITING DESA ALUE RAYA KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Zuriat Zuriat (Jurnal Marine Kreatif, 2018)
Alue Raya village is a subdistrict in Samatiga District that face directly with enough wide water that called river which there are several biota like crabs and fish that grew by mangrove plant including Rhizoporastylosa, RhizoporaapiculataBI danNypa fruticans. This coastal area also existed in some villages like Kuala Bubon and others that surrounded by river waters. The problem that experienced by fishermen that catch the crabs by using trap namely decreased production of crabs from year to year. Five years ago, the fishing yield still used for fulfilling their household necessesary with 2 – 4 kg/day. However, in 2017, the fishing yield only 1 – 2 kg/day. The priority problem is decreasing crabs stock in such water. To overcome this long term problem. Thus, it is necessary to undertaken crabs restocking  and the control of fishing activity with body size  and gonad maturity level. The community serving activity that undertaken including problem identification and forming  community group as well as to propose the proposal to west of Aceh Government for helping addition of crabs stock.